ANALISIS PERBEDAAN ABNORMAL RETURN SEBELUM DAN SESUDAH PERISTIWA POLITIK PADA SAHAM PERUSAHAAN LQ-45 DI BEI - Hidayat, Randy (Universitas muhammadiyah palembang, 2018)
This study aims to examine the information content of a political event (Gerakan AksiDamai 212 and King Salman's Visit) on capital market activity especially in BEI. Using 42company data, divided into 9 industry sectors by using method of event study. GerakanAksi Damai 212 of one different sectors and the arrival of King Salman of two differentsectors. These results indicate that the events of Gerakan Aksi Damai 212 and the arrivalof King Salman influenced investments made by investors, but not all sectorsexperienced significant investment differences, due to unforeseen price fluctuations.